Loop group schemes and Abhyankar’s lemma - Gille, Philippe (Comptes Rendus. Mathématique)
We define the notion of loop reductive group schemes defined over the localization of a regular henselian ring $A$ at a strict normal crossing divisor $D$. We provide a criterion for the existence of parabolic subgroups of a given type.